The Effect of Explicit Instruction on Students’ Personal Letter ‎Writing Skills - Aswin Sunardi; Salamah (JPI: Jurnal Pustaka Indonesia, 2023)
This study examines whether Explicit Instruction (EI) improves seventh-grade students’ personal-letter writing skills in Indonesian language classes. Using a quantitative design with descriptive and inferential analyses, we surveyed 30 students from SMP Negeri 08 Bengkulu City; EI served as the independent variable and writing outcomes as the dependent variable. Data were collected via a structured questionnaire and analyzed using standard parametric procedures. Results indicate a marked improvement in students’ personal-letter writing after EI was implemented, with a substantial proportion of the variance in outcomes attributable to the model (R² ≈ 0.828), and a highly significant test statistic (t = 11.590, p < .001). These findings support the effectiveness of EI for guiding students through goal setting, modeling, guided practice, and independent performance in a stepwise manner, thereby strengthening task clarity and procedural fluency. The study concludes that EI is a robust pedagogical option for improving personal-letter writing among junior-secondary learners and recommends its integration into routine instruction with appropriate teacher scaffolding. Future research should expand the sample and compare EI with alternative explicit, strategy-based, or collaborative approaches to determine relative efficacy across genres and learner profiles.